Efficacy of slope-adjusted curve number models with varying initial abstraction coefficient for runoff estimation. (2018) - Verma, Sangeeta; Singh, Anju; Mishra, Surendra Kumar; Singh, Pushpendra Kumar; Verma, Ravindra Kumar
The present study evaluated the efficacy of three slope adjusted CN2 models as well as original SCS-CN method using LISS-III and ASTER DEM data. The performance of these models was also evaluated for four different values of initial abstraction coefficient (λ), i.e., 0.05, 0.1, 0.2 and 0.3 for the Kalu watershed in Maharashtra, India using R 2 and RMSE. The results show that slope adjusted CN formulation given by the Sharpley and Williams (1990) (Model 2) for λ = 0.3 performed the best with lowest RMSE (10.88) and highest R 2 (0.8757) in comparison to the other models. On the contrary, original SCS-CN model performed the worst. Results also show that watershed slope is an important factor affecting runoff generation and hence due consideration should be given to it in planning of soil and water conservation structures. This study also revealed that RS and GIS techniques are useful for estimating as SCS-CN model input data to predict runoff more accurately.